Role and research progress of hip arthroscopy in the treatment of pre-collapse osteonecrosis of the femoral head - Liu, Guangnian; Chen, Xing; Weng, Zijing; Xiong, Huazhang; Dong, Liming (Frontiers in Surgery, 2025)
BackgroundThis study is to provide a detailed overview of the application value of hip arthroscopy in the treatment of pre-collapse ischemic necrosis of the femoral head (ONFH) and summarizes the latest research progress.MethodsUsing the search string [(“osteonecrosis of the femoral head” OR “avascular necrosis of the femoral head” OR ONFH) AND (hip arthroscopy OR arthroscopic)] in PubMed, we identified 69 records. After screening and exclusions, 54 studies were included in a comprehensive narrative review of ONFH and hip arthroscopy. The review focused on the application of hip arthroscopy in core decompression and head–neck fenestration grafting for ONFH, and summarized the management of concomitant intra-articular lesions and arthroscopy-related complications.ResultsAs a novel technique applied in the early stages of ONFH, hip arthroscopy remains in an exploratory phase. Current literature affirms its clinical effectiveness in treating early ONFH, highlighting advantages such as highly precise positioning, shorter surgical duration, rapid postoperative recovery, and minimal surgical trauma compared to traditional approaches. However, challenges arise due to the unclear surface landmarks for arthroscopic entry, leading to a prolonged learning curve and demanding a high level of technical expertise from surgeons. Simultaneously, satisfactory outcomes have been achieved in addressing intra-articular pathologies accompanying the hip joint, such as femoroacetabular impingement, synovitis, and joint effusion.ConclusionsThis review provides a systematic description of the role of hip arthroscopy in ONFH and summarizes the latest clinical applications of hip arthroscopy and its shortcomings.